Multiple introns in a deep-sea Annelid (Decemunciger: Ampharetidae) mitochondrial genome - Angelo F. Bernardino; Yuanning Li; Craig R. Smith; Kenneth M. Halanych (Scientific Reports, 2017)
Abstract Wood falls provide episodic fluxes of energy to the sea floor that are degraded by a species-rich benthic fauna. Part of this rich diversity includes annelid polychaetes but unfortunately, our understanding of such fauna is limited and their genetic variability and evolutionary origins remain poorly known. In this study, we sequenced complete mitochondrial genomes from three congeneric Decemunciger (Ampharetidae) individuals that had colonized multiple wood falls in the deep (~1600 m) NE Pacific Ocean. Mitochondrial gene order within Decemunciger was similar to the three other available Terebellomorpha genomes, consistent with the relatively conserved nature of mitochondrial genomes within annelids. Unexpectedly, we found introns within the cox1, nad1 and nad4 genes of all three genomes assembled. This is the greatest number of introns observed in annelid mtDNA genomes, and possibly in bilaterians. Interestingly, the introns were of variable sizes suggesting possible evolutionary differences in the age and origins of introns. The sequence of the introns within cox1 is similar to Group II introns previously identified, suggesting that introns in the mitochondrial genome of annelids may be more widespread then realized. Phylogenetically, Decemunciger appears to be a sister clade among current vent and seep deep-sea Ampharetinae.